The impact of stylolites and fractures in defining critical petrophysical and geomechanical properties of some carbonate rocks - Padmanabhan, E. (Springer Science and Business Media Deutschland GmbH, 2015)
Stylolites are partings within rocks that exhibit complex mutual column and socket interdigitization. This study was initiated since the impact of stylolites in defining critical geomechanical, fluid flow and petophysical properties is not well-known. A total of nine carbonate samples from Turkey and seven from Malaysia were used in this study. The carbonate rocks have varied composition and have heterogeneous distribution of certain components such as stylolites, fractures and algal remains. Fabric, presence of stylolites as well as fractures have a controlling effect on the stress response and the contractional strain of carbonates from Malaysia and Turkey. The formation of stylolites and the location of the stylolites are independent of the rock fabric and the applied stress. Faces with stylolites showed a high degree of variability in terms of thermal conductivity when estimated at various points. Samples from Malaysia that consisted of stylolites generally had low thermal conductivity values compared with the non-stylolitic faces. The current study indicates that the stylolites present in these rocks have the potential to increase the permeability of the carbonate rock. It is even more interesting to note that in the region immediately bordering the stylolites, is occupied by fractured calcite crystals. However, the varied surface roughness indicates that the boundary conditions which define fluid flow in porous media would be very different within this stylolitic region. Â© 2015, Springer International Publishing Switzerland.